An Enrichment Workshop using Argumentation-Based Forensic Chemistry Activities to Improve the Critical Thinking of Gifted Students - Mustafa Tuysuz; Ummuye Nur Tuzun (Journal of Science Learning, 2020)
This research aims to evaluate a workshop using argumentation-based forensic chemistry activities to enhance gifted students' critical thinking. A workshop program, consisting of seven argumentation-based forensic chemistry activities, was conducted with 20 students at a gifted school in Turkey.  A qualitative experimental design was used. An experiment or drawing activity was first carried out. Following this step, the gifted students reconstructed the activity as an argument after an extensive group discussion. The data collected in the student-constructed arguments and evaluation were analyzed for content. The study's findings show that argumentation-based forensic chemistry activities contributed positively to these gifted students' critical thinking development.